Identification of two novel bullous pemphigoid- associated alleles, HLA-DQA1*05:05 and -DRB1*07:01, in Germans - Schwarm, Christian; Gola, Damian; Holtsche, Maike M.; Dieterich, Anabelle; Bhandari, Anita; Freitag, Miriam; Nürnberg, Peter; Toliat, Mohammad; Lieb, Wolfgang; Wittig, Michael; Franke, André; Worm, Margitta; et al. (Orphanet Journal of Rare Diseases, 2021)
Bullous pemphigoid (BP) is the most common autoimmune skin blistering disease characterized by autoimmunity against the hemidesmosomal proteins BP180, type XVII collagen, and BP230. To elucidate the genetic basis of susceptibility to BP, we performed the first genome-wide association study (GWAS) in Germans. This GWAS was combined with HLA locus targeted sequencing in an additional independent BP cohort. The strongest association with BP in Germans tested in this study was observed in the two HLA loci, HLA-DQA1*05:05 and HLA-DRB1*07:01. Further studies with increased sample sizes and complex studies integrating multiple pathogenic drivers will be conducted.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Autoimmune blistering skin diseases; Bullous pemphigoid; Germans; GWAS; HLA